Polish Digital Nomads - Majewski, Marcin (Polski nomadyzm cyfrowy, 2022)
Digital nomadism reflects the new trend among young people who work remotely so they can follow their passions and travel. The main research goal was to find out the determinant of the choice of such a lifestyle by Poles. The subject of the research were digital nomads of Polish descent. The method of literature analysis and in-depth interviews on a sample of 40 respondents was used. The study showed that Polish digital nomads do not identify with a larger community as they face misunderstanding and distrust the help of those they meet during their travels. A typical digital nomad works in the IT, marketing or education industry, is a young person looking for adventure while travelling, and not paying much attention to housing conditions. Characteristic features are also minimalism and a reluctance to start a family. The main determinants of the choice of a nomadic lifestyle include, first of all, the dissatisfaction with the living conditions in Poland, and the willingness to change.
Ekonomia XXI Wieku = Economics of the 21st Century, 2022, Nr 25, s. 19-27
Keywords: tourism; remote work; digital nomadism; coworking; turystyka; praca zdalna; cyfrowy nomadyzm